Does pre-angiography Total ST-segment resolution reliably predict spontaneous reperfusion of the infarct-related artery in patients with acute myocardial infarction? - Zongsheng Guo (BMC Cardiovascular Disorders, 2019)
Abstract Background ST resolution (STR) after AMI is a non-invasive indicator of IRA reperfusion. We investigated whether pre-angiography STR predicted spontaneous IRA reperfusion in STEMI patients. Method Patients with STEMI undergoing primary PCI were recruited. Standard 12-lead ECG tracings were recorded at first medical contact, immediately prior to arterial puncture and 60 min after PCI. STR was classified as total (≥70%; group I), partial (≥30 and < 70%; group II) or none (< 30%; group III). Patients were followed up for 1-year. Results The final analysis included 349 patients (n = 77, 160 and 112 for groups I, II and III, respectively). Compared with groups I/II, pre-procedural TIMI flow in group III was less frequently grades 2 or 3 (P < 0.001). Pre-PCI STR ≥70% was an independent predictor of pre-PCI TIMI-3 flow (OR: 2.8; P < 0.001). Pre-PCI STR < 30% was independently associated with pre-PCI TIMI flow 0–2 (OR: 3.1; P < 0.001). STR = 35.55% seems to be an optimal cut off for pre-procedural TIMI-3 flow prediction with sensitivity 0.943, specificity 0.456, Youden index 0.399, P = 0.027. STR prior to PCI was inversely correlated with 1-year combined CV events rate. STR > 70% may predict a better clinical outcome. Conclusions Assessment of STR could potentially be used to stratify risk in patients with STEMI before PCI.